Faktor-Faktor yang Mempengaruhi Kinerja Finansial pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia - Ananda, Tiara Riszky; Immanuela, Intan; Purbandari, Theresia (JRMA | Jurnal Riset Manajemen dan Akuntansi, 2016)
This research is aimed to examine the influence of institutional ownership, an invesment decision, age, and the financial leverage against the financial performance. The population in this research is manufacturing company who enrolled in BEI in 2011-2013. The sample used in this research is 75 companies taken by applying the technique of purposive sample. Engineering analysis used to test the hypothesis. The technique analysis use double regression linear (multiple regression). The result of this research shows that the institutional ownership and age of the company significant on the financial performance while the decision of the investment and also financial leverage do not significant on the financial performance.